2017
DOI: 10.3889/oamjms.2017.071
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Risk Factors of Head Trauma with CT Scan Findings in Children with Minor Head Trauma Admitted to Hospital

Abstract: BACKGROUND:In emergency medicine for determining the intracranial injury (ICI) in children with head trauma, usually brain CT scan is performed. Since brain CT scan, especially in children, has some disadvantages, it is better to find a procedure which could help to choose only the children with real head trauma injury for brain CT scan.AIMS:The aim of this study is to find such procedure. This study was descriptive, analytic and non-interventional.METHODS:We reviewed the archived files of children with head t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…Thus we recommend performing brain CT scans in patients with mild TBI and scalp lacerations as the risk of intracranial pathologies in these patients is approximately high. This is in concordance with previous reports [6,8,11]. However, the role CT scan in evaluating the outcome of the patients with mild TBI has been a debate.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus we recommend performing brain CT scans in patients with mild TBI and scalp lacerations as the risk of intracranial pathologies in these patients is approximately high. This is in concordance with previous reports [6,8,11]. However, the role CT scan in evaluating the outcome of the patients with mild TBI has been a debate.…”
Section: Discussionsupporting
confidence: 82%
“…However, it has been demonstrated that there is no correlation with the clinical findings and the CT-scan findings in mild TBI especially in children [11]. The correlation between the scalp lacerations and the intracranial findings is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that men are more involved in business life than women. 2,4,8,9,12 Although the rate of males was higher before and after the pandemic in our study, no statistically significant difference was found between the genders (Table 1). We think this difference does not exist as all genders stay at home as active life is restricted due to Covid-19 isolation.…”
Section: Discussioncontrasting
confidence: 55%
“…The incidence of intracranial pathologies in children with head trauma was found to be b10% in most studies [5,7,18]. Although these pathologies vary from isolated skull fractures to epidural hematomas, the frequency of neurosurgical operation requirement is b1% [5].…”
Section: Discussionmentioning
confidence: 99%